Prognostic Biomarkers and Immunotherapeutic Targets Among CXC Chemokines in Pancreatic Adenocarcinoma - Huang, Jiacheng; Chen, Zhitao; Ding, Chenchen; Lin, Shengzhang; Wan, Dalong; Ren, Kuiwu (Frontiers in Oncology, 2021)
Background: Pancreatic cancer is one of the principal causes of tumor-related death in worldwide. CXC chemokines, a subfamily of functional chemotactic peptides, affect the initiation of tumor cells and clinical outcomes in several human malignant tumors. However, the specific biological functions and clinical significance of CXC chemokines in pancreatic cancer have not been clarified. Methods: Bioinformatics analysis tools and databases, including ONCOMINE, GEPIA2, the Human Protein Atlas, DAVID, GeneMANIA, cBioPortal, STRING, DGidb, MethSurv, TRRUST, SurvExpress, SurvivalMeth and TIMER, were utilized to clarify the clinical significance and biological functions of CXC chemokine in PAAD. Results: Except CXCL11/12, the transcriptional levels of other CXC chemokines in PAAD tissues were significantly elevated, and the expression level of CXCL16 was the highest among these CXC chemokines. Our findings also suggested that all of the CXC chemokines were linked to tumor-immune dysfunction involving the abundance of immune cell infiltration, and the Cox proportional hazard model confirmed that Dendritic, CXCL3/5/7/8/11/17 were significantly associated with the clinical outcome of PAAD patients. Furthermore, increasing expressions of CXCL5/9/10/11/17 were related to unfavorable overall survival (OS), and only CXCL17 was a prognostic factor for disease-free survival (DFS) in PAAD patients. And for the prognostic value of single CpG of DNA methylation of CXC chemokines in patients with PAAD, we identified 3 CpGs of CXCL1, 2 CpGs of CXCL2, 2 CpGs of CXCL3, 3 CpGs of CXCL4, 10 CpGs of CXCL5, 1 CpG of CXCL6, 1 CpG of CXCL7, 3 CpGs of CXCL12, 3 CpGs of CXCL14, and 5 CpGs of CXCL17 were significantly associated with prognosis in PAAD patients. Moreover, the prognostic value of CXC chemokines signature in PAAD were explored in two independent cohort, and results indicated that the patients in low-risk group had a better OS compared with the high-risk group. And survival analysis of the DNA methylation of CXC Chemokines signature demonstrated that PAAD patients in high-risk group had longer survival times. Conclusions: These findings reveal the novel insights into CXC chemokine expression and their biological functions in the pancreatic cancers, which might serve as accurate prognosis biomarkers and suitable immunotherapeutic targets for patients with pancreatic cancer.